The PcERF5 promotes anthocyanin biosynthesis in red-fleshed pear (Pyrus communis) through both activating and interacting with PcMYB transcription factors - Yao-jun CHANG; Guo-song CHEN; Guang-yan YANG; Cong-rui SUN; Wei-lin WEI; Schuyler S. KORBAN; Jun WU (Journal of Integrative Agriculture, 2023)
As there is a strong interest in red-skinned pears, the molecular mechanism of anthocyanin regulation in red-skinned pears has been widely investigated; however, little is known about the molecular mechanism of anthocyanin regulation in red-fleshed pears due to limited availability of such germplasm, primarily found in European pears (Pyrus communis). In this study, based on transcriptomic analysis in red-fleshed and white-fleshed pears, we identified an ethylene response factor (ERF) from P. communis, PcERF5, of which expression level in fruit flesh was significantly correlated with anthocyanin content. We then verified the function of PcERF5 in regulating anthocyanin accumulation by genetic transformation in both pear skin and apple calli. PcERF5 regulated anthocyanin biosynthesis by different regulatory pathways. On the one hand, PcERF5 can activate the transcription of flavonoid biosynthetic genes (PcDFR, PcANS and PcUFGT) and two key transcription factors encoding genes PcMYB10 and PcMYB114. On the other hand, PcERF5 interacted with PcMYB10 to form the ERF5-MYB10 protein complex that enhanced the transcriptional activation of PcERF5 on its target genes. Our results suggested that PcERF5 functioned as a transcriptional activator in regulating anthocyanin biosynthesis, which provides new insights into the regulatory mechanism of anthocyanin biosynthesis. This new knowledge will provide guidance for molecular breeding of red-fleshed pear.